PENGATURAN PENDIDIKAN PROFESI ADVOKAT DI INDONESIA - Mustakim Mustakim (Departemen Hukum Perdata, 2020)
The implementation of Professional Advocate Certification is deemed to be incompatible with the standards in organizing professional education as regulated by Law no. 20 of 2003 on the National Education System and Law no. 12 of 2012 on Higher Education, causing uncertainty and unscrupulous on the quality of prospective advocates, detrimental to the legal environment in whole. The Profession of Advocates possesses a strategic position in law enforcement to uphold justice, therefore this occupation is known to be a noble profession (offi cium nobile). The problem formulation in this research is to set the framework of implementing Professional Advocate Certifi cation to maintain the professionalism and integrity of advocates and to organize the implementation of Professional Advocate Certifi cation in the coming days. With the use of normative approach as the method of research by utilizing statutory regulations, court decisions, and legal concepts, this study found that Professional Advocate Certifi cation must be carried out in collaboration with universities in accordance with the mandate of the Constitutional Court Decision (MKRI) No. 95/PUU-XIV/2016 date 23rd of May 2017, Decision Number 46 P/HUM/2019, Thursday, 26th of September 2019 and Decision Number 87 P/HUM/2019 on the date 13th of December 2019 and Regulation of the Minister of Research, Technology, and Higher Education Number 5 of 2019. Therefore, it is crucial to accomplish fundamental changes concerning the implementation of advocate professional education by constructing curriculum changes leading up to the integrity and expertise in maintaining the noble reputation of the advocates’ role (officium nobile).